Analgesic effect of intravenous versus intraperitoneal dexmedetomidine as an adjuvant to intraperitoneal bupivacaine (0.125%) in laparoscopic cholecystectomy: a randomized, double blind, interventional study - Chitra Singh; Priyanka Jain; Pratibha Rathore; Harimohan Sharma; Shailja Bamniya (Journal of Applied Pharmaceutical Research, 2022)
Background and Aims: Laparoscopic cholecystectomy has emerged as a gold standard technique for gall bladder stones. The aim of the present study was to compare the analgesic effect of intravenous (IV) vs intraperitoneal (IP) dexmedetomidine as an adjuvant to intraperitoneal (IP) bupivacaine in laparoscopy. Methods: A prospective, randomized, double blind, interventional study was conducted on 100 patients undergoing laparoscopic cholecystectomy where they were divided into following 2 groups: Group A: Patients received IV 1µg/kg dexmedetomidine diluted to 30 ml with normal saline over 10 min and 40 ml of 0.125% bupivacaine IP after removal of gall bladder. Group B: Patients received IV 30 ml of normal saline and 1µg/kg IP dexmedetomidine in 40 ml of 0.125% IP bupivacaine after removal of gall bladder. The primacy outcome was noted as a difference in mean duration for need of first rescue analgesia. The total consumption of analgesic in first 24hours was recorded and compared between the two groups. Results: Both the groups were comparable in terms of demographic profile and intraoperative hemodynamic parameters with no statistical difference. Comparison of time to first analgesic requirement between the two groups showed statistically significant results with unpaired t test The time of first rescue analgesia in Group A was 151.80 min ± 76.624. and in Group B was 94.80min ± 21.499. The total analgesic requirement in 24 hours in Group A was 136.64 ± 31.251 and in Group B was 144.12 ± 21.49. Conclusion: In our study we concluded that intravenous dexmetomidine provided superior analgesia as compared to intraperitoneal dexmetomidine when used as an adjuvant with Bupivacaine intraperitoneally.